2012
DOI: 10.1002/ps.2318
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of global gene regulation in the Cry1Ab‐resistant and Cry1Ab‐susceptible strains of Diatraea saccharalis

Abstract: The large portion of metabolic- or catalytic-related genes with significant upregulations indicated a potential large increase in metabolic or catalytic activities in the Cry1Ab-RR strain. This cDNA microarray gene expression data could be used to characterize and identify new genes that may be associated with Bt resistance in D. saccharalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 64 publications
3
24
0
3
Order By: Relevance
“…The expression of this gene was up-regulated after ingestion of bacteria-contaminated diet in the cabbage semilooper [38] and a similar gene was found to be involved in prophenoloxidase activation and nodulation response in the cotton bollworm [46]. Interestingly, a gene of the same class (Hdd11) was found induced in the Cry 1Ab resistant sugarcane borer [47] and in the beet armyworm after ingestion of B. thuringiensis VIP toxins [48], indicating its importance in defence against B. thuringiensis .…”
Section: Resultsmentioning
confidence: 99%
“…The expression of this gene was up-regulated after ingestion of bacteria-contaminated diet in the cabbage semilooper [38] and a similar gene was found to be involved in prophenoloxidase activation and nodulation response in the cotton bollworm [46]. Interestingly, a gene of the same class (Hdd11) was found induced in the Cry 1Ab resistant sugarcane borer [47] and in the beet armyworm after ingestion of B. thuringiensis VIP toxins [48], indicating its importance in defence against B. thuringiensis .…”
Section: Resultsmentioning
confidence: 99%
“…For example, hdd11 was found to be highly induced in midguts of a Cry1Ab-resistant strain of Diatraea saccharalis [39], and Hdd23 was up-regulated in Lepidoptera infected by virus or bacteria [70,71]. Another gene of this family, Hdd1 , was also up-regulated in midguts of T. ni immune-induced by bacterial feeding [16].…”
Section: Resultsmentioning
confidence: 99%
“…This contrasts with studies performed in immune-induced lepidopterans (such as T. ni fed with bacteria [16]), or with coleopterans (such as T. molitor fed with Cry3Aa [34] or T. castaneum fed with Cry3Aa or Cry23Aa/Cry37Aa [37]), where apolipophorin III was up-regulated. Indeed, Cry1Ab-resistant D. saccharalis [39] showed constitutive up-regulation of an apolipophorin precursor. Typically, lipophorins I and II are considered insect hemolymph proteins involved in lipid transport, but lipophorin III has been also implied in defense mechanisms by clotting [21,61].…”
Section: Resultsmentioning
confidence: 99%
“…- Guo et al (2012) analysed gene regulation patterns in laboratory-selected Cry1Ab-resistant (Cry1Ab-R) and Cry1Ab-susceptible (Cry1Ab-S) sugarcane borer (SCB, Diatraea saccharalis) strains. Microarray analyses of 7145 cDNAs revealed 384 differentially expressed genes between larvae of the Cry1Ab-R and Cry1Ab-S strains.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…Maize MON 810 had less leaf damage, and fewer surviving larvae were recovered from the whole plant, compared to non-Btmaize plants. The authors concluded that maize MON 810 may be used to control ASB and SSB, but that its efficacy also needs to be evaluated under field conditions.- Guo et al (2012) analysed gene regulation patterns in laboratory-selected Cry1Ab-resistant (Cry1Ab-R) and Cry1Ab-susceptible (Cry1Ab-S) sugarcane borer (SCB, Diatraea saccharalis) strains. Microarray analyses of 7145 cDNAs revealed 384 differentially expressed genes between larvae of the Cry1Ab-R and Cry1Ab-S strains.…”
mentioning
confidence: 99%